Organogênese in vitro em Jatropha curcas L. - Lima, Magda Laiara Bezerra de (2013)
The physic nut (Jatropha curcas L.) is considered a potential source for the biofuel production, because of its high productivity and oil quality extracted from the seeds. However, its use is unfeasible for human and animal food due to antinutritional factors like the curcin protein and specially the secondary metabolites – phorbol esters. The application of biotechnological tools, like tissue culture, can be used to overcome these limitations. In this context, the aim of this work was to propagate whole plants in vitro using shoot cultures obtained from physic nut seeds germinated in vitro and in vivo; to determine the reproducibility of a regeneration protocol available in the literature, and to define through histological studies, the origin of the regenerated plant in vitro. For the in vitro propagation, shoots were used as explants sources, which were placed on MS medium supplemented with the cytokinins BAP (6- benzylaminopurine), KIN (kinetin) e 2-iP (2- isopentenyl adenine), 2,0 mg.L-1. BAP showed the best results in the development of the shoots. This regulator was used alone or in association with gyberelins for the elongation of the shoots. The indole-3-butyric-acid was used for the rooting. The supplementation of the medium culture with BAP was efficient in the development of the shoots and the elongation was superior with the use of GA3 alone. The rooting was achieved with AIB. To determine the reproducibility of an organogenesis protocol, cotyledons from physic nut seeds germinated in vitro were placed on MS medium supplemented with BAP and AIB for the promotion of aerial which were elongated with BAP and rooting with AIB. The cotyledonary explants were placed with the abaxial and adaxial face in contact with the medium to establish the best position of it in the in vitro regeneration. Whole plants of J. curcas L. were obtained using the protocol tested. The best position of the cotyledonar segment was the adaxial face in contact with the medium, where 56% of the explants formed shoots. The histological analysis was made with cotyledonary explants collected in sequential intervals of 0, 5, 10, 15 e 25 days of permanency in the regeneration medium. The anatomical study allowed the accompaniment of the organogenesis in physic nut, where parenchymal cells next to the adaxial region of the cotyledonar explants were divided and formed the shoots. The data obtained from this work showed that both protocols used, from shoots tips and cotyledonar explants, were efficient in the regeneration process; the histological analysis suggests that regeneration occurs via direct organogenesis and possibly presents multicellular origin.